Gestational and congenital toxoplasmosis in two hospitals in bogota, colombia (2014)
Background. Gestational toxoplasmosis is acquired duringpregnancy and involves a risk of the parasite crossing theplacenta, thereby leading to foetal infection, which can leadto serious sequelae in children, mainly chorioretinitis, cerebralcalcification, hydrocephalus and intellectual disability.Objective. Determining the prevalence of maternal andneonatal toxoplasmosis in women attending the Engativáand La Victoria hospitals in Bogota, Colombia, for delivery.Correlating the results with those of a national multicentrestudy. Determining IgM and IgA anti-toxoplasma prevalencein newborn (NB) umbilical cord blood.Materials and methods. This was a cohort study, which wasapproved by the participating institutions’ ethics committees.The patients signed informed consent forms and filled out asurvey requesting demographic and prenatal care data. A bloodsample was taken from the umbilical cord on delivery fordetermining anti-toxoplasma IgM. Anti-toxoplasma IgA wasalso measured in a subset of patients. Children suspected ofhaving either clinical or serological congenital toxoplasmosiswere followed-up for 12 months.Results. The study involved taking 3,224 NB umbilicalcord blood samples between April 1st 2009 and July 16th2010. Positive anti-toxoplasma IgG was found in 28.2% ofpregnant women (26.1-29.8 95%CI). Anti-toxoplasma IgMwas determined in 558 pregnant women and found positivein 34 patients (i.e. 1.1 per 100 NB gestational toxoplasmosisincidence). Nine blood samples were positive (7 for IgM and2 for IgA). Five of the NB studied (0.15%) were positive forIgG after 12 months’ follow-up, thereby confirming a diagnosisof congenital toxoplasmosis accounting for 1 in every 645live births.Conclusion. This study showed that 70% of the pregnantwomen were not infected with T. gondii in the chosen hospitalsin Bogotá. Gestational toxoplasmosis frequency was around 1%and 0.6% for congenital toxoplasmosis.